To find the last step after Jackson arrived at the equation \((-x) = -6\), we need to isolate \(x\).
Given \((-x) = -6\):
- To solve for \(x\), we can multiply both sides by -1, which will give us \(x = 6\).
Looking at the provided choices: A. Use Property of Equality to get x= (-6) - Incorrect B. Divide both sides by -1 to get x=6 - Correct C. Divide both sides by -1 to get x= (-6) - Incorrect D. Use Multiplication Property of Equality to get x=6 - This is not incorrect, but it's less precise than option B, which specifies division.
Therefore, the most appropriate answer is B. Divide both sides by -1 to get x=6.